Clinical characteristics, therapy response, and outcome of 51 adult patients with hematological malignancy-associated hemophagocytic lymphohistiocytosis: a single institution experience. Issue 8 (3rd August 2018) - Lorenz, Fryderyk; Klimkowska, Monika; Pawłowicz, Ewa; Bulanda Brustad, Agnes; Erlanson, Martin; Machaczka, Maciej
Abstract: Hemophagocytic lymphohistiocytosis (HLH) is an underdiagnosed but life-threatening syndrome of hyperinflammation often occurring in adults with hematological malignancies (hM-HLH). The aim of the study was to describe clinical characteristics, therapy response, and outcome of adults with hM-HLH. The study included 51 adults with hM-HLH aged 23–84 years. Hyperferritinemia ≥500 µg/L was present in 96% of patients. The serum concentration of sIL-2Rα ≥ 2400 U/mL was revealed in 94% of patients. Twenty-three patients (45%) responded to therapy and achieved remission of HLH. The probability of overall survival (OS) at 6, 12, 24, and 60 months after HLH diagnosis were 42, 20, 15, and 15%, respectively. Patients with HLH during chemotherapy showed longer OS (median 124 days) than the patients who had HLH solely attributed to malignancy (median 65 days), but this difference was not statistically significant. Awareness of HLH in lymphoid and myeloid malignancies is crucial for improved survival.